Efektifitas Brain Gym Double Doodle And Cross Crow Terhadap Perkembangan Kognitif Anak Usia 4-5 Tahun: Effectiveness of Brain Gym Double Doodle and Cross Crow on the Cognitive Development of Chlidren Aged 4-5 Years Old - Siswoariwibowo, Andika; Ishariani, Linda; Milhati, Milhati (Chakra Brahmanda Lentera Institute, 2025)
Cognitive development in early childhood is a critical foundation for learning success. However, data show that many Indonesian children under five have not reached their optimal cognitive potential. One method of stimulation that can be applied is Brain Gym exercises, specifically double doodle and cross crow movements. This study applied a quasi-experimental pretest-posttest design without a control group. A total of 21 children aged 4–5 years at Dharma Wanita 1 Darungan Kindergarten were selected using total sampling. The intervention lasted two weeks, consisting of 4 sessions of Brain Gym double doodle (30 minutes) and 4 sessions of cross crow (15 minutes). Cognitive development was measured using observation sheets and analyzed using the Wilcoxon test. Results: Before the intervention, most children (81.0%) had fair cognitive development. After the intervention, the majority (90.4%) were categorized as having very good development. The Wilcoxon test showed a significant effect with a p-value of 0.001 (p ≤ 0.05), indicating a significant impact of the intervention on children's cognitive development. Brain Gym double doodle and cross crow effectively stimulate integration between the brain's hemispheres through increased neural activity in the corpus callosum, improving cerebral blood flow and oxygenation. These findings support the use of these exercises as a simple and enjoyable stimulation method at home and school.